Hatchability of Nile crocodile (Crocodylus niloticus) eggs : association with bacteria and fungi in incubation boxes and in eggs that failed to hatch - Nothling, Johan O. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.